(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article deals with aphoristic expressions of Rostislav Dotsenko – Ukrainian writer, former political prisoner convicted for admiration of Ukrainian identity. Much attention is given to aphorisms that encourage to understanding human values and national priorities, to assessment of the socio-political and state processes. Author’s considerations are focused in artistic and semantic area of conceptual sphere «being» that actualizes appropriate lexemes, primarily life, death, eternity, instant, past, future, and so on. Aphorist appeals to those moral aspects of a human being which discredit him, because they contradict generally accepted standards of behavior distorting his strategy in society. A number of situational predefined samples are represented. They confirm the original author’s individual vision of some of those events, their emotional and critical assessment; serve as a versatile way to create a language picture of the world in general and in particular personally author’s